Perceived Parenting Style and Adolescents’ Social Anxiety in Selangor, Malaysia - Cong, Chin Wen; Aik, Chuah Peng; Rabbani, Mohtaram; Ni, Arianna Oh Zhing (Makara Human Behavior Studies in Asia, 2020)
Anxiety, especially social anxiety, is the most common mental health issue among Malaysian adolescents, and parenting styles have been suggested to play a crucial role in the development of adolescents’ anxiety symptoms. Therefore, this paper investigates the relationship between Malaysian adolescents’ perceptions of their parents’ parenting styles and their measured level of social anxiety, including differences by age and race. A total of 327 adolescents from international and national secondary schools in Selangor participated in this study. The Parental Perception Questionnaire and Kutcher Generalized Social Anxiety Disorder Scale for Adolescents were used to measure the adolescents’ perceptions of parenting styles and social anxiety, respectively. The results showed no significant correlations between parenting styles and social anxiety. In addition, parenting styles did not significantly predict the adolescents’ social anxiety. However, there were significant racial and age group differences in the categories of parenting style and levels of social anxiety. In conclusion, the parenting style received by Malaysian adolescents was not significantly related to their social anxiety. Interventions should focus on high-risk groups of adolescents (i.e., Malay adolescents and those aged 15–16 years old) to reduce their social anxiety.